Creativity in the pretend play of preschool children - Gardašević Ana (Nastava i Vaspitanje)
By using the potential of flexibility in play, a child learns to adapt to various situations that the modern world often requires by changing themselves and their environment. When adults support play, they help children express their creative potential. This paper presents a study to identify creative potential in pretend play and explore how adults contribute to play development. The method used was content analysis of narrative stories from pretend play sessions between children and an adult, recorded in a kindergarten group. The analysis focused on identifying the creative abilities that children express during play, as well as the ways in which adults contribute to play development by participating in it. The findings show that flexibility in play, fluency of ideas, and originality in solving problems that arise during play all enable the expression of creativity. Adults participating in play contribute to its development and expression of children's creative potential by helping to sustain initiated play, co-creating strategies with children in building the play together, maintaining the play context, interpreting values (such as fairness, responsible behavior, friendship, etc.) through dialogue with the children, being sensitive to children's initiatives and encouraging them. The results suggest that preschool teachers need to continuously reflect on and deepen their understanding of the connection between play and creativity and approach play as a co-creative space built together with children, while supporting the realization and development of their creative potential. In that way, they can help improve and evolve play practices in kindergarten settings.